Which factors are associated with extremely short‐term survival after surgery in patients with esophageal squamous cell carcinoma?. Issue 3 (25th May 2016) - Liu, Jingeng; Wei, Zhiru; Zhang, Jun; Hu, Wei; Ma, Zhenfei; Liu, Qinghang
Abstract: Aims: Esophageal squamous cell carcinoma (ESCC) is associated with a short median survival and low cure rates. The postoperative survival time of some patients with ESCC is extremely short. It is important to understand risk factors in subsets of patients associated with extremely short‐term survival. The standard factors such as T and N stage, which are predictive of actuarial survival, become less important as patients live for ≤1 year. However, the prevalence of these factors in these patient populations has not been well documented. We evaluated factors predictive of ≤1 year survival in this research. Methods: We analyzed 1596 patients underwent esophagectomy for ESCC retrospectively. The demographic and clinicopathologic characteristics were compared between patients who died within 1 year of esophagectomy and patients who survived more than 1 year after esophagectomy. Results: Univariate analysis showed significant differences between the two groups regarding gender, weight loss, comorbidity, neoadjuvant treatment, completeness of resection, pathological T stage, pathological N stage, histologic grade, the number of metastatic lymph nodes, postoperative complications, postoperative pulmonary infection and postoperative hospital stay. Based on logistic regression analysis, significant factors associated with extremely short‐term survival were male gender, incomplete tumor resection, higher pathological T stage, higher pathological N stage and postoperative pulmonary infection. Conclusion: The independent positive predictors for extremely short‐term survival are male gender, incomplete tumor resection and postoperative pulmonary infection besides higher pathological T stage and higher pathological N stage.